Pio hydato thorax of hepatic origin: bronchopleural fistula: intra-operative cardiac arrest; Severe respiratory insufficiency - Suiffet, Walter; Mañana, Julio; Irastorza, R (Cirugía del Uruguay, 2020)
Presented at session 1st November 1961